Evidence for specialist treatment of people with acquired brain injury in secure psychiatric services: systematic review and narrative synthesis - Liz Shaw; Michael Nunns; Simon Briscoe; Amelia Mosley; Daniel Dalton; Rob Anderson; Jo Thompson Coon (National Institute for Health Research, 2020)
Objectives: To systematically review evidence that can inform the arrangements for the specialist care of adults with ABI who may require secure psychiatric services. Data sources: Seven bibliographic databases (CINAHL, HMIC, MEDLINE, MEDLINE In-Process & Other Non-Indexed Citations, PsycINFO, Social Policy & Practice, ASSIA) were searched on 27th June 2019, date-limited to 2000. Database searches were supplemented with citation searching; inspecting relevant reviews; searching ClinicalTrials.gov and WHO International Clinical Trials Registry Platform, searching relevant websites; liaising with clinical experts and affiliation searches. Review methods: We sought evidence about adults with non-degenerative ABI placed in, eligible for referral to, or being assessed for eligibility for referral to secure psychiatric services in any high-income country. Eligibility for referral to secure services was based on assessment or observation of challenging behaviours. Psychometric studies of tools used in assessments were eligible for inclusion. Study selection, data extraction and quality assessment were completed independently by two reviewers. Given the heterogeneity of studies, outcomes and data, a narrative synthesis approach was used. We were interested in identifying patient, diagnostic or symptom characteristics associated with requiring care in secure settings. Findings: 6297 unique titles and abstracts were screened against inclusion criteria, leading to full-text screening of 325 papers. Forty-six observational and case-control studies and one systematic review were included; however none were set in, or referred explicitly to secure settings. Thirty-eight of the primary studies evaluated patient characteristics associated with challenging behaviour. Eight primary studies and the systematic review evaluated the psychometric properties of measures used to assess challenging behaviour. Narrative synthesis indicated a highly heterogeneous set of studies providing uncertain evidence about patient characteristics which may be associated with challenging behaviours. Whilst tentative associations were found between certain patient characteristics and occurrence of challenging behaviour, the conflicting nature of this evidence reduces confidence in these findings. There was no strong evidence to recommend the use of specific patient assessment tools. Limitations: We found no evidence regarding referrals to secure treatment settings and thus were not able to directly answer our research questions. Studies investigating associations between patient characteristics and challenging behaviours varied in methodological rigour and evidence was highly heterogeneous. Conclusions: There is no direct evidence to support decisions about the suitable setting for the care of adults with ABI who display challenging behaviour. There is tentative evidence about patient characteristics associated with risk of challenging behaviour. Future work: Primary research is needed to inform evidence-based decisions on the appropriate setting for the care of people with ABI who display challenging behaviour. Study registration: Open Research Exeter: http://hdl.handle.net/10871/40286 Funding: NIHR HS&DR programme. NIHR130320